2015
DOI: 10.1016/j.jcis.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation mechanism of amorphous silica nanoparticles: A simulation approach

Abstract: Hypothesis: Despite its importance in numerous industrial and natural processes, many unsolved questions remain regarding the mechanism of silica precipitation in aqueous solutions: order of the reaction, role of silica oligomers, existence of an induction time and characteristics of the particle population. This may be traced back, in past models, to the lack of account of the first stages of nucleation, size dependence of the growth law, and full particle population.Computational method: A microscopic descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The free energy differences between the two monomers and the dimer in both the pure water system and the system with NaCl (reactions Table 3.A.1 and 3.B.1) indicate that the dimer is slightly thermodynamically more favored, corresponding to a pK298 of -2.088 and -2.25, respectively. The direction of reaction favorability is similar to Noguera et al (2015) who computed pK303=-0.69. Some workers (Exley and Sjöberg, 2014;Sjöberg et al, 1981) however expressed that the monomer should be slightly more preferred.…”
Section: Discussion On H4sio4 + 27h2o +/-Nacl Systems: Zwitterion Formationsupporting
confidence: 84%
“…The free energy differences between the two monomers and the dimer in both the pure water system and the system with NaCl (reactions Table 3.A.1 and 3.B.1) indicate that the dimer is slightly thermodynamically more favored, corresponding to a pK298 of -2.088 and -2.25, respectively. The direction of reaction favorability is similar to Noguera et al (2015) who computed pK303=-0.69. Some workers (Exley and Sjöberg, 2014;Sjöberg et al, 1981) however expressed that the monomer should be slightly more preferred.…”
Section: Discussion On H4sio4 + 27h2o +/-Nacl Systems: Zwitterion Formationsupporting
confidence: 84%
“…107 Further systems in which the role of cluster-based precipitation pathways was reported include sodium acetate, 108 indium phosphide quantum dots, 109 CdS quantum dots, 110 atmospheric sulfuric acid/dimethylamine particles, 111 and Hf oxides. 112 Last but not least, silica precipitation characteristics are more complex than assumed by simple precipitation models, 113 which may be due to a precipitation mechanism according to the notions of the PNC pathway, as suggested previously based on a detailed literature review. 28 Indeed, solid-state NMR and cryo-TEM investigations indicated that the onset of aggregation in the silica system is based on the increase in Si−O coordination, 104 leading to a collapse of primary silica clusters, putatively rendering the silica PNCs less dynamic, as predicted by the PNC phase separation mechanism (Figure 3).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 94%
“…Amorphous silica forms via the condensation of silica monomers (H4SiO4) into Si-O-Si bonds (Iler, 1979), through polymerisation that can either occur at an interface (e.g., minerals, bacteria or plant matter) where it is described as "heterogeneous nucleation" or in the bulk fluid ("homogeneous nucleation") (Benning and Waychunas, 2007). In both cases, once silica nuclei have reached a critical size (< 0.5 to 2 nm, Iler, 1979;Noguera et al, 2015;Tobler et al, 2009), they grow spontaneously by the addition of silica from solution. Monomers are the dominant growth species (Bohlmann et al, 1976;Bremere et al, 2000;Mroczek and McDowell, 1988) due to their predominantly neutral charge (Ka 10 -8.8 at 120 C) (Fleming and Crerar, 1982;Seward, 1974) in the slightly alkaline pH regime of silica-rich geothermal waters.…”
Section: Introductionmentioning
confidence: 99%